Mesenchymal stem cell culture in aligned porous hydroxyapatite scaffolds using a multiwell plate bioreactor for bone tissue engineering. Issue 1 (10th September 2022) - G., Gayathry; R. K., Athira; M. S., Anju; P. R., Anil Kumar; P. R., Harikrishna Varma; Kasoju, Naresh; Komath, Manoj
Abstract: Regeneration of bone lost by trauma, diseases and aging, and restoration of its load‐bearing function are major clinical challenges. Hydroxyapatite (HA) is a clinically proven scaffold material for bone grafting, but the random‐pore structure limits the homing of the cells inside the graft and the bone regeneration progresses with the resorption of the graft material. This work is based on the hypothesis that aligned through pores in the graft will lead to a faster healing by homing the local cells inside and provide a better environment for new bone formation through the graft structure. The investigation was done using aligned porous HA scaffolds seeded with human Wharton's jelly‐derived mesenchymal stem cells (hWJ‐MSCs) and cultured in a multiwell format bioreactor setup. The cell adhesion was studied by microscopy, cell proliferation was evaluated by Alamar blue assay and osteogenic differentiation was confirmed by biochemical and molecular assays. The results indicate that the hWJ‐MSCs infiltrated through the aligned porous network of the scaffold, proliferated well when cultured in the expansion medium, and differentiated into osteogenic lineage when cultured in the differentiation medium. Abstract : The study presents a combinatorial bone tissue engineering approach involving human Wharton's jelly‐derived mesenchymal stem cells as the cells of choice, hydroxyapatite‐based aligned porous structure as the scaffold, and a multiwell format bioreactor for the cell culture. The results indicated successful infiltration, proliferation, and osteogenic differentiation of stem cells within the scaffold under the set dynamic culture conditions.